A Critical Study Of Contractor Liability in The Perspective of Maqashid Sharia And Islamic Contract Law - Helma Widya; Hermansyah Alam (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study critically examines the concept of contractor liability in construction projects from the perspective of Maqashid Sharia and Islamic contract law. In Islamic jurisprudence, contracts are binding moral and legal agreements, and the fulfillment of obligations by all parties, including contractors, is essential to uphold the values of justice, trust, and responsibility. Using a normative legal research method, this paper analyses classical and contemporary fiqh literature, as well as statutory regulations relevant to construction contracts. The study finds that contractor liability is not only a matter of legal obligation but also a reflection of ethical responsibility in line with the objectives of Sharia, particularly the protection of propertyand public welfare(maslahah). When a contractor fails to meet agreed standards or causes damage due to negligence or breach of contract, Islamic law provides clear mechanisms for accountability and compensation. The study concludes that integrating maqashidbased principles into contract enforcement can enhance fairness and sustainability in the construction industry, especially in Muslim-majority contexts.